Effect of ofloxacin levels on growth, photosynthesis and chlorophyll fluorescence kinetics in tomato - Zhang, Zhihuan (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.